Early child care, maternal labor supply, and gender equality: A randomized controlled trial - Henning Hermes; Marina Krauß; Philipp Lergetporer; Frauke Peter; Simon Wiederhold (Universität Augsburg, Institut für Volkswirtschaftslehre, 2024)
We provide experimental evidence that enabling access to universal early child care increases maternallabor supply and promotes gender equality among families with lower socioeconomic status (SES). Ourintervention offers information and customized help with child care applications, leading to a boost inchild care enrollment among lower-SES families. 18 months after the intervention, we find substantialincreases in maternal full-time employment (+160%), maternal earnings (+22%), and household income(+10%). Intriguingly, the positive employment effects are not only driven by extended hours at child carecenters, but also by an increase in care hours by fathers. Gender equality also benefits more broadly frombetter access to child care: The treatment improves a gender equality index that combines informationon intra-household division of working hours, care hours, and earnings by 40% of a standard deviation,with significant increases in each dimension. For higher-SES families, we consistently observe negligible,insignificant treatment effects.
urn:nbn:de:bvb:384-opus4-1139483
Keywords: J13; J18; J22; C93; 330; child care; maternal employment; gender equality; randomized controlled trial